2019
DOI: 10.21608/eajbsa.2019.26674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Ferro- Solution on Some Biological Aspects of Pectinophora gossypiella (Lepidoptera: Gel.)

Abstract: Entomology Journal publishes original research papers and reviews from any entomological discipline or from directly allied fields in ecology, behavioral biology, Sea-water, magnetic, ferrous sulphate and ferric chloride , Pectinophora gossypiella, and survived, fecundity and longevityThis study investigated the effects of four compounds included Sea-water (compound-1), Seawater +magnetic + traces of (mixture ) pure ferrous sulphate (FeSo4. 7 H2O) and ferric chloride (Fe cl3. 6H2O) 1:1 (compound-2), Seawater +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The obtained data are in agreement with many authors studied that the different magnetic powers against Lepidopterous insects, e.g., P. gossypiella, and Said et. al., (2017) and Earias insulana Kandil et al, (2018) they recorded the high increased in longevity females exposed to MF, on contrast the decreased in longevity males. Table 2.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The obtained data are in agreement with many authors studied that the different magnetic powers against Lepidopterous insects, e.g., P. gossypiella, and Said et. al., (2017) and Earias insulana Kandil et al, (2018) they recorded the high increased in longevity females exposed to MF, on contrast the decreased in longevity males. Table 2.…”
Section: Resultsmentioning
confidence: 92%
“…2014) recorded that the adults of Euproctis pseudoconspersa (EP), highly affected when it were exposed to electromagnetic field. Walters and Carstensen (1987) on fecundity and development in Drosophila, behavior and metabolism also, exposed the pupal stage of P. gossypiella to magnetic power (28mlt) increased the mortality and reduction the percent of adult emergence (Said et al 2017), MF high effected on survivor, longevity, viability and fertility of Earias insulana (Kandil et al, 2018) also, (Pan et al, 2004), development and viability (Biljana et al, 2001), longevity and fecundity of P. gossypiella (Said et al 2017),…”
Section: Introductionmentioning
confidence: 99%
“…Opposite, the eggs laying by treated adult female had severe reduction especially in high magnetic field treatment as well as fertility and fecundity. Moreover, Kandil, et al (2019) indicated that there was a significant negative effect on the reproductive process and sometimes leads to the failure of the reproduction process when the adults of P. gossypiella exposed to a magnetic field of 14&18 mlt. Also, Matar, et al (2018), stated that total eggs laid /female had a high decreasing in the number to 116.0, 79.9 and 132.0 eggs, when exposed to magnetic power (2.0, 10.0 & 24 mt), respectively, compared to 216.0 eggs in untreated.…”
Section: Table (4)mentioning
confidence: 99%
“…Some general reviews have reported on the effects and mechanisms of EMF exposure on insects [Hussein et al, 2015], new findings in the cell biochemistry of insects, and the impact of changes in insects' biology or population dynamics [Kandil et al, 2018, 2019]. Additional negative effects that were described in different studies included the direct exposure of adult Pectinophora gossypiella and E. insulana to magnetic power (42, 12, and 4.2 mT), showing that some biological aspects were affected, such as development time, malformation of different stages, and generation times [Said et al, 2017; Kandil et al, 2018, 2019], along with reduced reproductive ability and fertility [Balmori, 2015], lethargy, failure to find food, escape behavior, disturbance of the sense of orientation, and reduced reaction speed. The effect of MF on insect behavior, biochemical parameters, and the morphology of Lepidoptera, Spodoptera litouralles , Pectinophora gossypiella , and E. insulana were studied [Hussein et al, 2014; Balmori, 2015; Kandil et al, 2018].…”
Section: Introductionmentioning
confidence: 99%